ผลของการจัดกิจกรรมการเรียนการสอนคณิตศาสตร์ โดยใช้เทคนิค 4 MAT ที่มีต่อผลสัมฤทธิ์และความคิดสร้างสรรค์ทางคณิตศาสตร์ ของนักเรียนชั้นมัธยมศึกษาปีที่ 3 - นัฎฐิตา โพธิ์เพชร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To compare the mathematics learning achievements of mathayom suksa three students before and after being taught by organizing mathematics instruction activity using the 4 MAT technique. To compare the mathematics learning achievements of mathayom suksa three students between groups being taught by organizing mathematics instruction activity using the 4 MAT technique and being taught by conventional approach. To compare the mathematical creativity of mathayom suksa three students before and after being taught by organizing mathematics instruction activity using the 4 MAT technique. And to compare the mathematical creativity of mathayom suksa three students between groups being taught by organizing mathematics instruction activity using the 4 MAT technique and being taught by conventional approach. The subjects were mathayom suksa three students in academic year 2002 in Watrachabopit School, Bangkok Metropolis. There were divided into two groups, one with 50 students in experimented group and the other with 47 students in controlled group. The experimental group was taught by organizing mathematics instruction activity using the 4 MAT technique and the control group was taught by conventional approach. The research instruments were the mathematics learning achievement test and the mathematical creativity test. The data were analyzed by means of arithmetic means, standard deviation and t-test. The research results were revealed that 1. The mathematics learning achievement of mathayom suksa three students being taught by organizing mathematics instruction activity using the 4 MAT technique after the experiment was higher than that before the experiment at 0.05 level of significance. 2. The mathematics learning achievement of mathayom suksa three students being taught by organizing mathematics instruction activity using the 4 MAT technique was higher than that being taught by conventional approach at 0.05 level of significance. 3. The mathematics creativity of mathayom suksa three students being taught by organizing mathematics instruction activity using the 4 MAT technique after the experiment was higher than that before the experiment at 0.05 level of significance. 4. The mathematics creativity of mathayom suksa three students being taught by organizing mathematics instruction activity using the 4 MAT technique was higher than that being taught by conventional approach at 0.05 level of significance.